Lexical Stratification of “The Tale of Igor’s Campaign” - Nikolaev, Sergei L. (Slověne, 2014)
This paper deals with the problem of dialect in The Tale of Igor’s Campaign. The author places great emphasis on lexical stratification. Dialectally marked vocabulary in The Tale is associated with only two areas of the East Slavic dialect continuum: 1) the South Eastern area (Southwest Russian, Belarusian, and Ukrainian dialects) and 2) the Northern area (Russian dialects originating in Pskov and Novgorod). Distribution of dialect words in The Tale is uneven: the South Western items characterize the main part of the text and the Northern elements prevail in some fragments. Although the presence of dialectal vocabulary in The Tale has long been established, a complementary distribution of the South Western and Northern items has not yet been observed. Grammatical analysis of The Tale shows that 1) its text dates from before the end of the 13th century, and 2) its dialect may be localized in the Pskov-Polotsk zone, perhaps in its South Pskov or Toropets-Selizharovo areas. At the same time, the grammar of The Tale lacks typical South Western features, and there arises the problem of contradictory evidence of grammar and vocabulary. Perhaps the dilemma may be solved by going beyond the bounds of purely linguistic research into The Tale’s text.